Effectiveness of Nursing Interventions and Nurses' Competencies in the Use of Chemoport in Cancer Patients: A Systematic Review - Lisna, Lisna; Allenidekania, Allenidekania; Edison, Chiyar (Poltekita : Jurnal Ilmu Kesehatan, 2024)
Chemoport is an implanted device, placed in the central venous system especially for infusion of chemotherapy drugs in oncological diseases that can reduce vascular inflammation during chemotherapy because this device is implanted under the skin, making IV (intravenous) drug administration easier and reducing pain. Nurses as officers must be able to provide more specific care and therapy based on patient needs, and must understand the lives of cancer patients and their families. The purpose of this study was to determine the effectiveness of nursing interventions and nurse competence in the use of chemoport in cancer patients.  The research method used a systematic review with article searches on five trusted journal databases, such as EBSCOhost, ClinicalKey Nursing, Sage Journal and Science direct. Article analysis using the PRISMA method. The results showed that there were ten articles that fit the criteria for articles related to nursing interventions and nurse competence in the use of chemoport in cancer patients. All articles used quantitative research methods with a randomized control trial design. The conclusion is that nursing interventions and nurse competence in the use of chemoport in cancer patients, among others, are divided into nursing interventions to reduce pain, namely virtual reality interventions, giving Valsalva maneuvers, skin stimulation, and giving local anesthesia. While nursing interventions to reduce anxiety include virtual relity interventions, visual blocking information interventions and patient education and nurse competence through increasing nurse knowledge and providing training.